Vaccine wastage in Nigeria: An assessment of wastage rates and related vaccinator knowledge, attitudes and practices. Issue 48 (4th December 2017) - Wallace, Aaron S.; Willis, Fred; Nwaze, Eric; Dieng, Boubacar; Sipilanyambe, Naawa; Daniels, Danni; Abanida, Emmanuel; Gasasira, Alex; Mahmud, Mustapha; Ryman, Tove K.
Highlights: In Nigeria, we assessed vaccine wastage-related vaccinator knowledge and practices. Mean vaccine wastage rates were between 18 and 35%, varying little by vaccine type. Measles-containing vaccine was administered in 63% of sessions and DTP3 in 84%. Vaccinators wait for at least 6 children before opening measles-containing vaccine. 30% of caregivers had been turned away at least once for vaccination of their child. Too much focus on reducing wastage leads to missed opportunities for vaccination. Abstract: Introduction: The introduction of new vaccines highlights concerns about high vaccine wastage, knowledge of wastage policies and quality of stock management. However, an emphasis on minimizing wastage rates may cause confusion when recommendations are also being made to reduce missed opportunities to routinely vaccinate children. This concern is most relevant for lyophilized vaccines without preservatives [e.g. measles-containing vaccine (MCV)], which can be used for a limited time once reconstituted. Methods: We sampled 54 health facilities within 11 local government areas (LGAs) in Nigeria and surveyed health sector personnel regarding routine vaccine usage and wastage-related knowledge and practices, conducted facility exit interviews with caregivers of children about missed opportunities for routine vaccination, and abstracted vaccine stock records and vaccination session data over a 6-month period to calculate wastage rates and vaccine vial usage patterns. Results: Nearly half of facilities had incomplete vaccine stock data for calculating wastage rates. Among facilities with sufficient data, mean monthly facility-level wastage rates were between 18 and 35% across all reviewed vaccines, with little difference between lyophilized and liquid vaccines. Most (98%) vaccinators believed high wastage led to recent vaccine stockouts, yet only 55% were familiar with the multi-dose vial policy for minimizing wastage. On average, vaccinators reported that a minimum of six children must be present prior to opening a 10-dose MCV vial. Third dose of diphtheria-tetanus-pertussis vaccine (DTP3) was administered in 84% of sessions and MCV in 63%; however, the number of MCV and DTP3 doses administered were similar indicating the number of children vaccinated with DTP3 and MCV were similar despite less frequent MCV vaccination opportunities. Among caregivers, 30% reported being turned away for vaccination at least once; 53% of these children had not yet received the missed dose. Discussion: Our findings show inadequate implementation of vaccine management guidelines, missed opportunities to vaccinate, and lyophilized vaccine wastage rates below expected rates. Missed opportunities for vaccination may occur due to how the health system's contradicting policies may force health workers to prioritize reduced wastage rates over vaccine administration, particularly for multi-dose vials.